Право громадян на охорону здоров'я - Бутрин-Бока, Наталія; Іванчук, Мирослав; Butryn-Boka, N.; Ivanchuk, М. (ТНЕУ, 2018)
Досліджено деякі аспекти права громадян на охорону здоров’я. Зазначено, що враховуючи сучасний стан національного медичного законодавства та проведення низки реформ у галузі медицини, ця проблематика являється архіактуальною. Здійснено правовий аналіз та зроблено певні висновки. This article is devoted research of some aspects of right for citizens on the guard of zdorovya. Recognition the modern state of national medical legislation and to the leadthrough of row of reforms in industry of medecini, this problematika appears arkhiaktual’noy. For this reason, authors carried out a legal analysis and did certain conclusions.
A right for citizens on a health protection
Keywords: право громадян; медична допомога; охорона здоров’я; медична реформа; right for citizens; medicare; health protection; medical reform